Sustainability In Construction In The UAE - Al Fahim, Ahmed Taha (2020)
The realization of the construction projects is dependent on the successful realization of a large set of criteria. Among them, the key role is played by the following parameters: budget and schedule requirements to the project, quality characteristics, and security of potential stakeholders that will utilize the construction facility in the future. Due to the definition of the rising role of sustainability in operations of the business, the criteria of sustainability were also identified as an important requirement for the construction project in different countries, including the UAE. In this dissertation, this paper aims to provide a complex and detailed answer to the range of questions in the sphere of sustainable waste management for construction projects in the UAE. The significance of this theme was defined with the rising demand for realization of the construction projects in the country, and the associated increase of risk level for the organizations and stakeholders in the sphere of waste management. For the aims of the study, the following research questions were addressed: definition of key construction and demolition waste streams in the construction sector of the UAE; assessment of the potential impact of construction waste on the environment in the UAE; definition of the existing rules and legal regulations applied to the organization of sustainable waste management in the UAE; and definition of required and recommended changes to the existing practices in waste management for the UAE construction sector to make it more sustainable. To implement the stated research objectives, the procedure of the study was divided into four key stages - literature review, the quantitative method applied through the survey that was distributed to the sample size of 106 participants, the analysis of the results, and the generation of recommendations. In the context of the literature review, the following questions were addressed: definition of different types of construction and demolition waste in the UAE construction sector; the disposal of the waste streams; assessment of the potential impact of different types of construction waste on the environment; comparison of types of waste sources that are properly and improperly managed in the UAE; existing rules and regulations applied for waste management segment of the UAE construction sector; specific statistics describing the problem of waste management in the UAE; specific factors that lead to ineffective waste management and recommendations that could be applied to guarantee an improved quality of waste management in the UAE construction sector. The results of the literature review had to contribute to a full understanding of the current situation in the sphere of waste management in the UAE and abroad. Results of the literature review defined the actual level of the issue’s significance, key sources of problems, and potential solutions that could be applied for the aims of recommendations development. A quantitative study of primary data collection from 106 participants had to contribute to the definition of the actual situation from the point of view of employees and management operating in the UAE construction sector. The following groups of stakeholders engaged in the UAE construction sector were applied for the study: developer, contractor, consultant, government, and private sector. According to the results, a major part of the participants was aware of sustainability issues in their sphere of work. The effectiveness of sustainability practices applied in their work was assessed as high by the majority of participants. Among the factors of waste management, respondents considered the factors of cost, productivity, waste reduction, and adequate skills as most important. Participants agreed that both private business and government should pay much more attention to the sphere of waste management in the construction sector. Among the benefits of effective construction waste management, participants of the study-oriented on the factors of cost reduction, increased productivity, improved health, waste minimization, environmental protection, better life quality, and better use of materials. Based on the study findings, specific recommendations were developed for the UAE construction sector in general. Following findings are important to mention: the need for companies to work toward recycling of construction waste materials; the need for the government to develop a set of clear and transparent rules for the regulation of waste management procedures; requirement for a business to increase the level of awareness and education of employees on the issues of sustainable waste management; and prioritization of reuse of the construction waste materials. Taken together, these measures should contribute to the transformation of waste management practices in the UAE for higher productivity and effectiveness.